DIGITAL-ТЕХНОЛОГІЇ ЯК СУЧАСНІ ІНСТРУМЕНТИ СИСТЕМИ УПРАВЛІННЯ У ПІДПРИЄМСТВАХ ІНДУСТРІЇ ГОСТИННОСТІ - Fostolovych, Valentyna (Zhytomyr Ivan Franko State University, 2022)
The intensive pace of digital transformation creates the need to respond quickly to changes in needs, interests, tools, which are preferred by hospitality customers. From the point of view of business efficiency, digitalization is focused on integrating artificial intelligence, software products into the production process and the process of effective management decisions to solve current situations and solve problems based on ready-made decision algorithms based on real performance indicators. By adapting software resources to the work of enterprises and ensuring not only our own economic security, but above all, we form an unprecedented value to the consumer, assessing their needs and personally meeting their requirements, standards and wishes. This approach helps to increase the level of competitiveness of the enterprise in the market, which is extremely important especially for the hospitality industry, where you need a personal approach to each client. Often, hospitality companies carry out several activities, and the management of the entire production process should be organized in a single technological cycle, for the convenience of the client. It is with the help of software products that it becomes possible to combine completely different technological processes of separate divisions or departments of the enterprise into a single system with the ability to differentiate each type of work and evaluate the results of their activities and individual business processes. Modern software products make it possible to ensure the synergistic effect of the work of separate structural units or even branches of companies. The rapid development of software products encourages companies to move to an innovative type of development, trying to be the first to adapt new tools to their own business. By linking all systems into a single mechanism, we have real-time analytical data that allows us to: track the strengths and weaknesses of the business; understand the economics of the whole process of providing services and be able to quickly correct situations; focus on those channels from which users are most converted to real customers. Therefore, it is important to explore the basic tools of digital technologies that can be effectively used in the process of doing business and increase its competitiveness.